Oxidative peeling of carbon black nanoparticles. Issue 112 (28th October 2015) - Wilson, Peter M.; Orange, François; Guinel, Maxime J.-F.; Shekhirev, Mikhail; Gao, Yang; Colon Santana, Juan A.; Gusev, Alexander A.; Dowben, Peter A.; Lu, Yongfeng; Sinitskii, Alexander
Abstract : We demonstrate that layered carbon black nanoparticles can be oxidatively peeled via the reaction with potassium permanganate in sulfuric acid. Abstract : We demonstrate that layered carbon black nanoparticles can be oxidatively peeled via the reaction with potassium permanganate in sulfuric acid. As a result of this reaction, outer layers of carbon nanoparticles "peel" off due to high levels of oxidation while the less oxidized inner cores, though they exhibit remarkable solubility in water, remain mostly intact.